Development of Traditional Japanese Game Media (Budhi Dharma) in Group Guidance Services to Prevent Bullying Behavior - Fadilla Zalzabila Lubis; Abdurrahman Abdurrahman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Bullying remains a major challenge in school environments because it negatively affects students' social, emotional, and academic development. This study aimed to develop the Japanese traditional game media Budhi Dharma as a group guidance medium to prevent bullying behavior among students at SMP Negeri 2 Hinai. The study employed a Research and Development approach using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants were 10 students selected through purposive sampling based on recommendations from the school counselor. Data were collected through expert validation questionnaires, student response questionnaires, observations, documentation, and pretest–posttest instruments. Data were analyzed using descriptive percentage analysis and a paired sample t-test to examine the effectiveness of the developed media. The findings revealed that the Budhi Dharma game media was categorized as highly feasible, obtaining a score of 90% from the material expert and 86% from the media expert. Students also provided highly positive responses, with an overall score of 88%, indicating high levels of participation, enthusiasm, collaboration, and understanding during group guidance activities. Furthermore, the effectiveness test showed a significant improvement in students' anti-bullying understanding and attitudes, with the mean score increasing from 61.80 (pretest) to 87.60 (posttest). The paired sample t-test yielded Sig. (2-tailed) = 0.001 (p < 0.05), confirming a statistically significant difference between pretest and posttest scores. These findings indicate that the Budhi Dharma traditional game media is valid, practical, and effective for supporting group guidance services in preventing bullying behavior. The novelty of this research lies in integrating a Japanese traditional game into structured group guidance services, combining cultural values with collaborative learning to strengthen empathy, communication skills, cooperation, emotional regulation, and anti-bullying attitudes among junior high school students.